Supporting and Obstacling Factors of Communication Planning in Management of COVID-19 in Bima Town - Eko Nurfahmi; Hafied Cangara; Jeanny Maria Fatimah (International Journal of Social Service and Research, 2022)
Covid-19 is a disease outbreak that is contagious throughout the world. Everyone feels the bad impact of this pandemic, both developing countries and Indonesia are no exception. Covid-19 has spread to all regions in Indonesia, including Bima Town. Bima Town is the east gate to enter the NTB area. Bima Town was able to handle this pandemic well, as evidenced by being the only area in NTB that is included in the Green Zone. This disease outbreak that has spread widely has greatly affected the life of creatures on this earth, such as the social, religious, economic, political and so on. Prevention efforts continue to be carried out by the Bima Town government as a form of government responsibility for the impacts and dangers of this pandemic on people's lives. This study aims to determine the factors that hinder and support the government's efforts in preventing and overcoming the dangers of Covid-19 in Bima Town by using a qualitative approach research method where the method used is a case study that departs from the handling of the Covid-19 pandemic carried out by the government. This is in accordance with the aim of the researcher to describe, analyze and explain the communication planning of a local government in the Town of Bima, West Nusa Tenggara. The research technique used is purposive sampling, which is a technique to find and determine informants by means of researchers selecting certain people who are considered to be able to provide the data needed then based on data or information obtained from informants. The results of the research that hampered the performance of the task force in preventing Covid-19 in the Town of Bima were social media that discussed issues about the untruth of Covid-19 so that people became paranoid. But in reality the public is able to accept when the government tries to educate and socialize so that it can minimize all what is stigmatized such as preparing vaccines, supporting infrastructure, budgets, public spaces that are able to be well maintained and education both through social media and other media.